Augmentation of intramedullary nail in unstable intertrochanteric fractures with plate or cable - Zhao, Yanrui; Wang, Hanzhou; Liu, Yang; Shan, Lei; Zhou, Junlin (Frontiers in Surgery, 2024)
Abstract Backgrounds: This study aims to evaluate the clinical outcome of intramedullary nail supplemented by buttress plate or cable in the treatment of intertrochanteric fracture with broken lateral wall. Methods: From May 2015 to January 2022, patients with unstable intertrochanteric femoral fractures underwent intramedullary fixations strengthened with buttress plates or cables, which depended on the lateral femur wall fragment type. The clinical and radiographic results were compared between the two groups. The hip function was evaluated according to the Harris Hip Scoring (HHS) system. Results: Forty-one patients who sustained intertrochanteric fracture + broken lateral wall were enrolled. Of these, thirty-four received a minimum of twelve months of follow-ups. No statistically significant differences in baseline and operative data were proved between these groups (p>0.05). Three patients were observed fat liquefaction after surgery (plate group: 2 cases, cable group: 1 case). All patients could sustain partial/ full weight-bearing and no case underwent subsequent operation. The HHS of the last follow-up presented 83.6±4.9 points in the plate group and 83.8±3.7 points in the cable group. Conclusions: Intertrochanteric femoral fracture with broken lateral wall is an unstable injury type, the operative treatments of which have been challenging and controversial over the years. Augmentation of intramedullary nailing system using plate/ cable contributes to reconstructing the lateral femur wall. Keywords: unstable intertrochanteric femoral fractures, lateral femoral wall, intramedullary nail fixation, clinical outcome, Harris Hip Scoring system.